"Knowing Your Status and Knowing Your Partner's Status Is Really Where It Starts": A Qualitative Exploration of the Process by Which a Sexual Partner's HIV Status Can Influence Sexual Decision Making. Issue 6 (24th July 2017) - Bird, Jason D. P.; Morris, Joseph A.; Koester, Kimberly A.; Pollack, Lance M.; Binson, Diane; Woods, William J.
Abstract : Gay and bisexual men are at disproportionate risk for human immunodeficiency virus (HIV) infection. While prevention efforts often emphasize consistent condom use, there is growing evidence that men are using seroadaptive safer-sex strategies, such as serosorting and seropositioning. This qualitative analysis of 204 HIV-negative and HIV-positive gay and bisexual men explored the ways that a sexual partner's HIV status can influence safer-sex strategies and sexual decisions. The majority of the respondents reported that they were influenced by their partners' HIV status. Those respondents who reported no influence discussed adhering to safer-sex rules that were not dependent on partner status and a lack of concern about HIV. Conversely, respondents who reported influence identified three primary areas of influence: psychological impacts, partner preference and selection, and specific behavioral intentions and strategies. A conceptual model explicating a potential process by which respondents use partner serostatus information in shaping sexual decisions is presented.